Motivasi dan Prestasi Belajar Siswa di Indonesia: Kajian Meta-Analisis - Sofwan Adiputra; Mujiyati Mujiyati (Konselor, 2017)
This article discusses the relevance of students' motivation and achievement in samples in Indonesian. Motivation is the drive, the desire, the individual needs to do an activity. The level of one's motivation can be traced through the behavioral background, it is also found in the learning motivation. Motivation to learn to form achievement motivation which is an effort to achieve the best result of learning by referring to a standard of education quality. This study aims to perform meta-analysis on 20 research results in Indonesia about the relevance of motivation to learning achievement. The analysis was performed by bare bone’s meta-analysis method. The results showed the correlation analysis of the population after corrected by the sample error analysis, estimated at 0.457, the population variance of 2.42 with the standard deviation of 1.55. Referring to a 95% confidence interval with an acceptance limit between -2,581 <ρ<3.495 and a value of ρ 0.457. Based on it can be concluded that there is influence between motivation to student achievement in Indonesia.